2016
DOI: 10.1016/j.actao.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Giraffe browsing in response to plant traits

Abstract: Intake rates by large herbivores are governed by among other things plant traits. We used Masai giraffe (Giraffa camelopardalis tippelskirchi Matschie) as study animals, testing whether they as very large browsers would follow the Jarman-Bell principle and maximize intake rate while tolerating low forage quality. We worked in Arusha National Park, Tanzania. We investigated how intake rate was determined by bite mass and bite rate, and show that bite mass and bite rate were determined by plant characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Unlike carnivores that hunt elusive but nutritionally balanced food (Charnov, ), most large herbivores have to compose their diet by combining a varying set of small meals characterised by relatively low nutritional value and high nutritional heterogeneity (e.g., Cates & Orians, , Mahenya, Kambinda, Marie, & Skarpe, ). Variability in the nutritional value of forage may increase in tropical systems as compared with temperate ones, making food selection particularly important for browsing herbivores in tropical arid and semi‐arid ecosystems (Zemmelink & Mannetje, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike carnivores that hunt elusive but nutritionally balanced food (Charnov, ), most large herbivores have to compose their diet by combining a varying set of small meals characterised by relatively low nutritional value and high nutritional heterogeneity (e.g., Cates & Orians, , Mahenya, Kambinda, Marie, & Skarpe, ). Variability in the nutritional value of forage may increase in tropical systems as compared with temperate ones, making food selection particularly important for browsing herbivores in tropical arid and semi‐arid ecosystems (Zemmelink & Mannetje, ).…”
Section: Introductionmentioning
confidence: 99%
“…Its narrow muzzle, flexible upper lip and long tongue enable it to strip off twigs or select individual leaves or leaf clusters between thorns (Gurevitch et al 2006, Milewski et al 1991, Pellew 1983). However, Mahenya et al (2016) found giraffe to have higher biting rate in species with spines. Spines tended to slow down biting rate by impala in Serengeti but not in Mikumi.…”
Section: Discussionmentioning
confidence: 99%
“…At each monthly passage along the six transects, we carefully and visually checked all tree and shrub species (predominantly growing higher than 0.5 m) present along the 500-m transect on a 5-m band on either side. This direct visualization approach is commonly used in the study and identification of browsed species (Chevrier et al 2012 ; Mahenya et al 2016 ; Borkowski et al 2017 ; Breslau et al 2020 ; Chebli et al 2020 ). The cumulative number of the fresh browsing traces (the color of the sectioned part of the plant is still green; Fig.…”
Section: Methodsmentioning
confidence: 99%